Análise comparativa entre técnicas de controle digital aplicadas ao acionamento de motor de indução trifásico alimentado por sistema fotovoltaico de estágio duplo - Baldissera, Gabriel Casanova (2022)
In order to apply photovoltaic energy sources to power induction motors without connection to the electrical network, and to provide control of the parameters of this motor, a study was carried out on dual-stage photovoltaic systems for autonomous systems. Thereunto, the model of the single diode photovoltaic panel was adopted as the photovoltaic energy source of the system. The source feeds a DC-DC boost converter, which is controlled to keep the voltage supplied by the source close to its reference value, providing maximum power to the system. The boost converter supplies power to the DC bus, to which a bank of batteries is connected through a bidirectional buck-boost converter, the bidirectional converter control is carried out to control the bus voltage, thus, the battery operates in discharge mode and in load mode to keep the voltage close to the reference value, and to meet the motor demand in varying weather conditions. Ultimately, the three-phase induction motor is powered from the DC-AC inverter, which is powered through the DC bus. To control the induction motor, some digital control techniques are applied to the inverter, and then a comparative analysis is carried out between the most used control techniques for driving three-phase induction motors. Therefore, from system simulations, and with the comparative analysis of digital control techniques, it is possible to define which technique can be used for better efficiency and effectiveness of an autonomous system, which depends on the application in which the system is inserted.